Four new species of Lysianassidae Dana, 1849 (Crustacea: Amphipoda) From Northeastern Brazilian coast - Sorrentino, Rayane; Moraes, Elienai E.b.; Senna, André R. (Zootaxa, 2019)
Material collected from three different states of the northeastern region of Brazil (Ceará, Rio Grande do Norte and Bahia) is analyzed. Four new lysianassid species of the genera Aruga and Shoemakerella are described. This paper includes the first record of Aruga in Brazilian waters and an identification key to world species of Aruga and Shoemakerella.